Coastal aquaculture management of research and development coastal aquaculture center region 3, Takhianthong Subdistrict, Kanchanadit District, Surat Thani Province, Thailand - Sangaewut, Ponlakrit (Linguistics and Culture Review, 2022)
The objectives of this research were: 1) to study the management of coastal aquaculture at the Coastal Aquaculture Research and Development Center, Region 3, Surat Thani Province; 2) study problems and obstacles in aquaculture management. 3) Guidelines for the development of aquaculture management. This research used both qualitative and quantitative methods simultaneously. The sample consisted of 60 people, and a categorical randomization method was used. The qualitative method used a focus group and selected five key informants specifically. The research instruments used include questionnaires and semi-structured interviews. The Quantitative data analysis used statistics such as; mean, percentage and standard deviation. The results showed that the overall opinion on the management of coastal aquaculture Research and Development Center, Region 3 (Surat Thani) was at a high level with a mean of 4.03. The qualitative research method used in-depth interviews with the sample groups; it was found that coastal aquaculture management can be of two types: 1) The government sector co-ordinates with some agencies and organizations to seek the people’s opinions in unity, which shows a direct collaboration with the government, hence opening room for mutual understanding. Both in terms of giving information, problem-solving, expression of opinion, and joint decision.